Dengue Haemorrhagic Fever. A Problem of Clinical Diagnosis and Proposal for Using a Scoring Systetn - Muzief Munir; Tjandra Husada; I. Mustadjab (Indonesian Pediatric Society, 1982)
This prospective study was conducted in an attempt to find out a method ofclinical diagnoS'is of Dengue Haemorrhagic Fever wi,th high accuracy and coverage.A clinical picture of all cases admitted with 3 days fever of unknown originand poS'itive tourniquet test was studied.The cardinal signs and symptoms i.e. liver enlargemerz.t, thrombocyte counJ.hematocrit, spontaneous bleeding such as epistaxis, petechiae, hematonw and hematemesis, were thoroughly studied from the day of admission up to the sixth dayof illness.Blood was drawn into filter-paper disks for serologic examination on the dayof admission, then 5, and 10 days thereafter.Based on a series of serological tests, the patients were grouped into confirmedand false DHF.Liver enlargement was found in both groups, but only in the confinned DHFgroup was it significantly related to the day of illness (r = 0.45, with probablyerror of 0.03 ).